The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1002/jat.1593
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of lemongrass (Cymbopogon citratus STAPF) essential oil on DNA damage and carcinogenesis in female Balb/C mice

Abstract: This study investigated the protective effect of oral treatment with lemongrass (Cymbopogon citratus STAPF) essential oil (LGEO) on leukocyte DNA damage induced by N-methyl-N-nitrosurea (MNU). Also, the anticarcinogenic activity of LGEO was investigated in a multi-organ carcinogenesis bioassay induced by 7,12-dimethylbenz(a)antracene, 1,2-dimethylhydrazine and N-butyl-N-(4-hydroxibuthyl)nitrosamine in Balb/C female Balb/c mice (DDB-initiated mice). In the short-term study, the animals were allocated into three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 54 publications
1
31
0
Order By: Relevance
“…The major compounds of the EO from Cymbopogon citratus were identified by GC/MS (Bidinotto et al, 2010) as follows: citral (a mixture of the cis and trans isomers -neral and geranial) followed by myrcene and geraniol. According to Vale et al (2002), citral and myrcene were not able to modify parameters of anxiolytic activity in mice, as evaluated by the elevated plus maze.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The major compounds of the EO from Cymbopogon citratus were identified by GC/MS (Bidinotto et al, 2010) as follows: citral (a mixture of the cis and trans isomers -neral and geranial) followed by myrcene and geraniol. According to Vale et al (2002), citral and myrcene were not able to modify parameters of anxiolytic activity in mice, as evaluated by the elevated plus maze.…”
Section: Discussionmentioning
confidence: 99%
“…Other compounds detected in the EO include geraniol (1.28%), 6-methyl-5-hepten-2-ona (0.64%), and undecan-2-one (0.29%), as detailed in Bidinotto et al (2010).…”
Section: Essential Oil Compositionmentioning
confidence: 99%
“…R.Br. ex G.Don Viral hepatitis A and C (Guinnin et al, 2015); liver damage Fever (Clement et al, 2015) Protective effect of the oil on DNA damage and carcinogenesis in female Balb/C mice (Bidinotto et al, 2011) ; Cardioprotective effect by biochemical and histopathological changes in experimentally induced cardiotoxicity (Gayathri et al, 2011) Hepatoprotective effect of the aqueous extract against hydrogen peroxide-induced liver injury in male rats (Rahim et al, 2014); alleviation of carbon tetrachloride-induced hepatic oxidative stress and toxicity (Koh et al, 2012) Morinda lucida Benth.…”
Section: Azadirachta Indica a Jussmentioning
confidence: 99%
“…Using comet assay some in vivo studies have shown the antigenotoxic effects of dietary agents, namely, artepillin C (a polyphenolic acid found in Brazilian green propolis and Baccharis dracunculifolia) (Azevedo Bentes Monteiro Neto et al, 2011), safranal, (a constituent of Crocus sativus L. stigmas) (Hosseinzadeh and Sadeghnia, 2007), orange juice (Franke et al, 2005b) and vitamin C (Franke et al, 2005a) against DNA damage induced by methyl methanesulfonate (MMS). Also lemongrass protected leukocytes from DNA damage induced by N-methyl-N-nitrosurea (MNU) (Bidinotto et al, 2010). Data from application of comet assay in the assessment of genoprotective effects of diet against alkylating DNA damage is limited.…”
Section: Whole Foodsmentioning
confidence: 99%